2014
DOI: 10.1186/s13550-014-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and advantage of adding 131I-MIBG to 90Y-DOTATOC for treatment of patients with advanced stage neuroendocrine tumors

Abstract: BackgroundPeptide receptor radionuclide therapy (PRRT) is an effective form of treatment for patients with metastatic neuroendocrine tumors (NETs). However, delivering sufficient radiation dose to the tumor to result in a high percentage of long-term tumor remissions remains challenging because of the limits imposed on administered activity levels by radiation damage to normal tissues. The goal of this study was to evaluate the dosimetric advantages of adding 131I meta-iodobenzylguanidine (131I-MIBG) to 90Y DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
(36 reference statements)
0
10
0
1
Order By: Relevance
“…The addition of 131 I-MIBG to 90 Y DOTA-Phe1-Tyr3-octreotide ( 90 Y-DOTATOC) in patients with advanced stage midgut NETs confirmed the feasibility of this strategy. 27 Of particular interest is how these findings will translate to new PRRT agents that possess higher target affinities than traditional SSTR agonists. In a small pilot study a SST2-receptor antagonist, 177 Lu-DOTA-JR11, was shown to possess superior intratumoural residence time and higher tumour uptake over 177 Lu-DOTA-TATE; properties that make it well-suited to a radiosensitisation strategy.…”
Section: Peptide-based Trtmentioning
confidence: 99%
“…The addition of 131 I-MIBG to 90 Y DOTA-Phe1-Tyr3-octreotide ( 90 Y-DOTATOC) in patients with advanced stage midgut NETs confirmed the feasibility of this strategy. 27 Of particular interest is how these findings will translate to new PRRT agents that possess higher target affinities than traditional SSTR agonists. In a small pilot study a SST2-receptor antagonist, 177 Lu-DOTA-JR11, was shown to possess superior intratumoural residence time and higher tumour uptake over 177 Lu-DOTA-TATE; properties that make it well-suited to a radiosensitisation strategy.…”
Section: Peptide-based Trtmentioning
confidence: 99%
“…In einer größeren retrospektiven Studie bei 98 Patienten [587] mit metastasierten NEN konnte ein medianes Überleben von 2,3 Jahren nach MIBG-Therapie erzielt werden, als häufigste Nebenwirkung wurde eine relevante Knochenmarkstoxizität bei 13 % der Patienten beschrieben. Bisher existieren keine vergleichenden Studien zwischen I-131-MIBG-Therapie und PRRT, jedoch wurde über eine höhere erzielbare Tumordosis durch eine kombinierte Behandlung mit I-131-MIBG und Y-90-DOTATOC berichtet [588]. Über Fallberichte hinausgehende Ergebnisse zur Sequenztherapie liegen jedoch nicht vor.…”
Section: Empfehlung Konsensunclassified
“…So far, only few studies have reported the combined use of different radiopharmaceuticals for TRT [ 26 ]. Previous studies performed TRT of neuroendocrine tumors via the combined use of high-energy and long-path 90 Y-somatostatin analog with its medium energy and short path 177 Lu analog for combating tumors of various sizes [ 27 ], or with 131 I-metaiodobenzylguanidine (a norepinephrine analog) for increasing the dose delivered to the tumor site [ 28 ]. Different from their treatment concepts, the present study suggested the combination of different radiopharmaceuticals (may not be limited to the currently used agents) to improve the intratumoral radioactivity distribution and thus enhance the therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%